2015
DOI: 10.1038/nature15727
|View full text |Cite
|
Sign up to set email alerts
|

Force generation by skeletal muscle is controlled by mechanosensing in myosin filaments

Abstract: Contraction of both skeletal muscle and the heart is thought to be controlled by a calcium-dependent structural change in the actin-containing thin filaments, which permits the binding of myosin motors from the neighbouring thick filaments to drive filament sliding. Here we show by synchrotron small-angle X-ray diffraction of frog (Rana temporaria) single skeletal muscle cells that, although the well-known thin-filament mechanism is sufficient for regulation of muscle shortening against low load, force generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
441
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 274 publications
(465 citation statements)
references
References 25 publications
23
441
0
1
Order By: Relevance
“…This work, by combining sarcomere-level mechanics with nanometermicrometer-scale X-ray diffraction in intact trabeculae from the rat cardiac ventricle, describes the changes in the thick filament and the myosin motors after force development in the cardiac twitch and their relation to SL, with the subnanometer precision achieved by using the X-ray interference between the two halves of the thick filament. We find that, in diastole, all of the myosinbased reflections mark the quasihelical three-stranded symmetry followed by the myosin molecules when they are in their off state on the surface of the thick filament with a short periodicity (2,4,7). At the peak of twitch force, the intensities of all of the meridional reflections and that of the ML1 decrease because of the myosin motors leaving their helical tracks as the thick filament switches on.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This work, by combining sarcomere-level mechanics with nanometermicrometer-scale X-ray diffraction in intact trabeculae from the rat cardiac ventricle, describes the changes in the thick filament and the myosin motors after force development in the cardiac twitch and their relation to SL, with the subnanometer precision achieved by using the X-ray interference between the two halves of the thick filament. We find that, in diastole, all of the myosinbased reflections mark the quasihelical three-stranded symmetry followed by the myosin molecules when they are in their off state on the surface of the thick filament with a short periodicity (2,4,7). At the peak of twitch force, the intensities of all of the meridional reflections and that of the ML1 decrease because of the myosin motors leaving their helical tracks as the thick filament switches on.…”
Section: Discussionmentioning
confidence: 92%
“…2A and Fig. S2A) shows the first-order layer line reflection (ML1) at an axial spacing of 43 nm and up to the sixth order of the meridional reflections (M1-M6) indexing on the quasihelical three-stranded symmetry with 43-nm periodicity followed by the myosin molecules when they are on the surface of the thick filament in their resting (off) state (2,4,7). The spatial resolution achieved along the meridian (parallel to the trabecula axis) with vertically mounted trabeculae is adequate to record the reflection fine structure (Fig.…”
Section: Sl-tension Relationmentioning
confidence: 99%
See 2 more Smart Citations
“…Shifts in these peaks, as would be induced by mechanical loading or ionic treatments, are therefore a measure of the nanoscale fibril strain demonstrated for vertebrate tissues (41-43, 46, 47). By combining micromechanics with in situ small-angle X-ray scattering, it has been possible to shed light on the fundamental ultrastructural mechanisms enabling viscoelasticity, toughness, and force generation in vertebrate tissues ranging from tendon (48), bone (44,46), and aorta (49) to muscle (50), as well as more unusual examples of biological optimization such as armored fish scales (43). Using SAXD, it was found that in crosslink-deficient fibrils, increased molecular slippage led to larger fibril strains, compared with normal collagen fibrils (48); that high toughness of antler bone was due to inorganic/organic friction at the intrafibrillar level (41); and that fibrillar reorientation blunted crack propagation in skin (51), among other examples.…”
Section: Significancementioning
confidence: 99%